Pour un grenelle de l'Unedic : refonder l'indemnisation du chômage - Crémieux, Robert; Gélot, Didier; Lanoizelez, Christine; Mezzi, Dominique; Moreau, Marc; Pelletier, Willy; Villiers, Claire; Zediri, Malika (Paris : Syllepse, 2003)
Bibliotheek François Vercammen
Frans
Monografie